PROFIL PARTISIPASI POLITIK MASYARAKAT PERSPEKTIF KEWARGANEGARAAN POLITIK (STUDI KASUS PEMILIHAN KETUA RT DI DESA ANJIR SERAPAT TIMUR, KABUPATEN KAPUS) - Ainiah, Siti; Sarbaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the profile of community political partiscipation from a political citizenship perspective in the neighborhood associantion (RT) head election in Anjir Serapat Timur village, Kapuas regency, which was conducted through a door to door mechanism. The study focuses on participation levels, formal and informal forms of participation and internal and external factors influencing citizen political local political partiticaption as an indicator practices at teha commnunity level. The study employed a qualitative descriptive approoch, with data collection techniques including observatin, interviews and documentation. Inforrmants included the village head, village officials, Rt head, community leaders, and farmer group administrators. Data analysis was conductes through data reduction, presentation and drawing conclusions, with validity rested through triangulation and member cheking. The results indicate that the level of community political participation is hgh, characterized bby widespread use of voting right, However, this is not entirely based on personal considerations, influenced by social relantionships, kinship and the dominance of local leaders. Form of participation include formal activities such as voting and deliberation, as well as informal activities through more dominant social interaction. Factors that influence participaion include internal aspects in the form of political foundations, educatiion, political effricacy, trust and economic conditions, as well as external aspects in the form of door to door election systems, the influence of community leaders and kinship relations.